2018
DOI: 10.1002/chem.201705398
|View full text |Cite
|
Sign up to set email alerts
|

N‐Terminal Cu‐Binding Motifs (Xxx‐Zzz‐His, Xxx‐His) and Their Derivatives: Chemistry, Biology and Medicinal Applications

Abstract: Peptides and proteins with N-terminal amino acid sequences NH -Xxx-His (XH) and NH -Xxx-Zzz-His (XZH) form well-established high-affinity Cu -complexes. Key examples are Asp-Ala-His (in serum albumin) and Gly-His-Lys, the wound healing factor. This opens a straightforward way to add a high-affinity Cu -binding site to almost any peptide or protein, by chemical or recombinant approaches. Thus, these motifs, NH -Xxx-Zzz-His in particular, have been used to equip peptides and proteins with a multitude of function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
203
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 109 publications
(222 citation statements)
references
References 101 publications
(255 reference statements)
9
203
0
4
Order By: Relevance
“…The existence of the minor CuHL complex is ascertained from the absorption trace at 685 nm; the absence of a corresponding signal in CD spectra is indicative of a macroloop structure, with the Cu 2+ ion coordinated to the N‐terminal amine and an imidazole nitrogen . The CuH −1 L and CuH −2 L species share all spectroscopic properties, both being typical ATCUN complexes isostructural with the N‐terminal site of HSA . The p K a of transition from CuH −1 L to CuH −2 L is consistent with the deprotonation of the nonbonding terminal carboxylate, elevated due to the decrease in the complex charge compared with the free peptide.…”
Section: Figurementioning
confidence: 81%
See 1 more Smart Citation
“…The existence of the minor CuHL complex is ascertained from the absorption trace at 685 nm; the absence of a corresponding signal in CD spectra is indicative of a macroloop structure, with the Cu 2+ ion coordinated to the N‐terminal amine and an imidazole nitrogen . The CuH −1 L and CuH −2 L species share all spectroscopic properties, both being typical ATCUN complexes isostructural with the N‐terminal site of HSA . The p K a of transition from CuH −1 L to CuH −2 L is consistent with the deprotonation of the nonbonding terminal carboxylate, elevated due to the decrease in the complex charge compared with the free peptide.…”
Section: Figurementioning
confidence: 81%
“…Human serum albumin (HSA) is the most abundant serum protein in the blood and acts as a carrier for numerous cargo molecules including lipids, hormones, metabolites, drugs and essential and toxic metals . It also contains an N‐terminal site (NTS) for binding divalent copper ions, which contains the amino‐terminal copper and nickel (ATCUN) motif, comprising a H 2 N‐Xaa‐Yaa‐His sequence . Albumin is a part of an elaborate copper‐trafficking machinery consisting of two groups of copper carriers .…”
Section: Figurementioning
confidence: 99%
“…Moreover, adding an N-terminal ATCUN motif to different AMPs can enhance the activity of these peptides by inducing ROS formation [46]. Moreover, previous studies also indicated that the Cu(II)-ATCUN complex can damage DNA, RNA, proteins and lipids because it induces ROS generation [72][73][74]. Therefore, ROS are important for AMPs to killing of microbial pathogens [75][76][77][78] and are possibly generated through a Fenton-like reaction involving the Cu(II)-ATCUN complex [74,79].…”
Section: Discussionmentioning
confidence: 99%
“…Libardo e colaboradores (2014) adicionaram às sequências dos peptídeos anoplin (GLLKRIKTLL 10 -NH 2 ), pró-apoptótico (PAP; KLAKLAKKLAKLAK 14 -NH 2 ) e shbuforin (RAGLQFPVGRVHRLLRK 17 -NH 2 ) os motivos ATCUN ("DAH" ou "GGH" ou induz a produção de EROs e danos à membrana mitocondrial/fosfolipídios, devido ao motivo ATCUN "DSH" em sua sequência peptídica que possibilita a coordenação de tais íons em geometria quadrada planar distorcida (HARFORD;SARKAR, 1997;MELINO et al, 2014;GONZALEZ et al, 2018). De fato, elevada atividade pró-oxidante da Hst 5 foi observada quando em presença de íons Cu 2+ (CABRAS et al, 2007).…”
Section: Análises Por Espectroscopia De Dicroísmo Circularunclassified
“…Atualmente, o estudo da possibilidade de aumentar a atividade e estabilidade de AMPs na presença de íons metálicos divalentes e a procura por sondas intracelulares destes íons, principalmente íons Cu 2+ (associado à angiogênese e progressão tumoralvide item 4.2.1. ), vem sendo intensificados (LIBARDO et al, 2014;DENOYER et al, 2015;GONZALEZ et al, 2018;ŁOBODA; ROWIŃSKA-ZYREK, 2018). Da mesma forma, a doença de Alzheimer também tem sido associada a um desequilíbrio destes íons, em especial Zn 2+ , Fe 3+ e Cu 2+ , que são acumulados nas placas amiloides depositadas no cérebro através da coordenação com o peptídeo Aβ (CHEN et al, 2006;HU et al, 2016;KEPP, 2017).…”
Section: Análises Por Espectroscopia De Dicroísmo Circularunclassified